SLAM-to-BIM con Stonex X120GO: Stonex presenta il nuovo laser scanner SLAM X120GO, un alleato perfetto per l’acquisizione rapida e precisa di dati per ottenere modelli 3D utilizzabili per il BIM - Ponti, Chiara (GEOmedia, 2022)
The digitalisation of the building process is increasingly present on the world scene. The methodology that leads to 3D models of construction projects and buildings is called BIM (Building Information Modelling). This methodology has the great advantage of associating different types of information (spatial, temporal, structural, etc.) with the three-dimensional model, thus making it possible to create an information system that can be shared between the various stakeholders involved in the design and construction process of a building. The BIM model also becomes the basis for the development of the so-called Digital Twins, models that integrate information on the use of the building over time and provide important analysis tools for maintenance planning. The surveying methodologies for the creation of BIM most widely used today are photogrammetry and laser scanner surveying. In both cases, the product of the survey are point clouds, i.e. sets of measured points that contain information on the position of the surveyed elements and possibly their colour. Point clouds are an extremely suitable product for BIM, as they are already three-dimensional and can be queried. However, in the case of large buildings or environments with special features, surveys with traditional static lasers (on tripods) can require long time. For this reason, in recent years, the world of topographic surveying has adopted innovative instruments that allow data to be acquired in motion, thus reducing scanning and processing times, the SLAM laser scanners. Stonex has developed a solution that combines precise sensors with a robust SLAM algorithm to produce clean, and accurate point clouds easily usable for BIM creation: the new SLAM X120GO laser scanner. This system features a 360° rotating LiDAR head capable of generating a point cloud coverage of 360° x 270°. In combination with IMU data and the SLAM algorithm, it is able to obtain high-precision threedimensional point cloud data of the surrounding environment without light and GPS. Equipped with three 5MP cameras to generate a horizontal 200°FOV and vertical 100°FOV, it can synchronously obtain texture information and produce colour point clouds and partial panoramic images. Both features are very useful in the BIM authoring phase. With a range of 120 m, the X120GO is suitable for working both indoors and outdoors, even in challenging environments, allowing the survey of an entire building to be completed with a single instrument. The X120GO has an integrated structure that makes it easy to move around the scanning environment. Thanks to the GOapp Android application, you can manage the scanner and observe the creation of the point cloud in real time. Once the start button is pressed, the X120GO can begin operations immediately, making data acquisition efficient and convenient. During data acquisition, the X120GO is also able to collect control point coordinates, which can then be combined with known points to georeference scans.